Tectonic strain recorded by magnetic fabrics (AMS) in plutons, including Mt Kinabalu, Borneo: A tool to explore past tectonic regimes and syn-magmatic deformation. (February 2019) - Burton-Johnson, A.; Macpherson, C.G.; Muraszko, J.R.; Harrison, R.J.; Jordan, T.A.
Abstract: Tectonic strain commonly overprints magmatic fabrics in AMS (Anisotropy of Magnetic Susceptibility) data for plutonic rocks produced by both compressional and extensional regimes. Mt Kinabalu, Borneo, is a composite pluton with an exceptional vertical range of exposure and clearly defined internal contacts. We show that tectonic fabrics are recorded pervasively throughout the intrusion, even near contacts, and present a workflow distinguishing compressive and extensional syn-magmatic deformation. At Mt Kinabalu this reveals a pervasive tectonic fabric indicating NW-SE Miocene extension in Borneo at 7.9–7.3 Ma, later than previously recognised, oriented NW-SE at 319° ±13.1°. Comparing data from Mt Kinabalu with data from globally distributed studies shows that tectonic strain is commonly recorded by plutons. Therefore, AMS fabric can be used to identify the syn-magmatic tectonic setting and combined with both geochronology and evidence for paleomagnetic rotation to provide a powerful tool for accurate determination of syn-magmatic tectonic regimes and strain orientations within temporal frameworks. Highlights: The tectonic fabric in the AMS data of Mt Kinabalu, Borneo, reveals NW-SE extension (319° ± 13.1°) between 7.9–7.3 Ma. Tectonic strain fabrics are far more ubiquitous in global plutonic fabrics than previously recognised. Tectonic strain recorded by AMS fabrics in dated plutons allows determination of past tectonics within a temporal framework.